Innovation concerns in horizontal mergers: - Marcos Puccioni de Oliveira Lyra; Camila Cabral Pires-Alves (Revista de Defesa da Concorrência)
Objective: this paper investigates how Cade – the Brazilian antitrust authority – has addressed innovation concerns in merger assessments, using antitrust literature and the experiences of the United States and the European Commission as reference points.